Morphological and chemical transformations of single silica-coated CdSe/CdS nanorods upon fs-laser excitation. Issue 14 (29th March 2017) - Albrecht, Wiebke; Goris, Bart; Bals, Sara; Hutter, Eline M.; Vanmaekelbergh, Daniel; van Huis, Marijn A.; van Blaaderen, Alfons
Abstract : Silica-coated CdSe/CdS NRs deform and transform chemically upon fs-laser and electron beam irradiation. Abstract : Radiation-induced modifications of nanostructures are of fundamental interest and constitute a viable out-of-equilibrium approach to the development of novel nanomaterials. Herein, we investigated the structural transformation of silica-coated CdSe/CdS nanorods (NRs) under femtosecond (fs) illumination. By comparing the same nanorods before and after illumination with different fluences we found that the silica-shell did not only enhance the stability of the NRs but that the confinement of the NRs also led to novel morphological and chemical transformations. Whereas uncoated CdSe/CdS nanorods were found to sublimate under such excitations the silica-coated nanorods broke into fragments which deformed towards a more spherical shape. Furthermore, CdS decomposed which led to the formation of metallic Cd, confirmed by high-resolution electron microscopy and energy dispersive X-ray spectrometry (EDX), whereby an epitaxial interface with the remaining CdS lattice was formed. Under electron beam exposure similar transformations were found to take place which we followed in situ .